Approximate Fixed Point Theorems for the Class of Almost S-KKM𝒞 Mappings in Abstract Convex Uniform Spaces. (16th June 2009) - Chang, Tong-Huei; Chen, Chi-Ming; Huang, Yueh-Hung
Abstract : We use a concept of abstract convexity to define the almostS -K K M 𝒞 property, al -S -K K M 𝒞 ( X, Y ) family, and almostΦ -spaces. We get some new approximate fixed point theorems and fixed point theorems in almostΦ -spaces. Our results extend some results of other authors.